Reconstruction of Teachers' Strategies in Cultivating Honest Character through Physics Learning: A Systematic Synthesis Based on Values, Affective, and Cognitive - Raden Muhammad Afrialdi; Astalini Astalini; Dwi Agus Kurniawan (Integrated Science Education Journal, 2026)
Purpose of the study: Study aims to systematically synthesize teachers' strategies in developing students' honest character through physics learning and to identify effective strategy patterns, research gaps, and directions for developing character-based learning in the modern learning era. Methodology: This study used a Systematic Literature Review (SLR) approach with the PRISMA protocol. A total of 29 reputable journal articles published between 2020 and 2025 were analyzed, sourced from Google Scholar, ERIC, Scopus, and DOAJ. Data were analyzed using thematic synthesis to group findings based on pedagogical strategies, teacher roles, assessment design, and affective and moral dimensions in physics learning. Main Findings: The study results show that honest character can be effectively developed through project-based learning, authentic assessment, experimental reflection, formative feedback, and the integration of moral values ​​into the scientific process. Teachers act as value facilitators, connecting cognitive, affective, and moral dimensions. Furthermore, digital literacy and ethical technology policies are important supporting factors in maintaining academic integrity. Novelty/Originality of this study: The novelty of this research lies in the formulation of an integrative conceptual framework that positions honesty as a core value in scientific process-based physics learning. Limitations of this research include its reliance on secondary sources and the paucity of long-term empirical research specifically examining the impact of honesty-based physics strategies.